Hawksbill turtles visit moustached barbers: cleaning symbiosis between eretmochelys imbricata and the shrimp stenopus hispidus - Sazima, Ivan; Grossman, Alice; Sazima, Cristina [UNESP] (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2004)
This seems to be the first record of cleaning symbiosis between marine turtles and shrimps. During their foraging on the reef flat, the turtles regularly visited and posed at the stations. The same stations were visited by a few species of reef fishes, which posed and were cleaned by the shrimps. We suggest that cleaning symbiosis between turtles and shrimps is widespread and went unrecognised due to the superficial resemblance between a resting turtle and a posing and cleaned one. Additionally, we submit a putative origin for the cleaning symbiosis between marine turtles and cleaner shrimps following a few simple behavioural steps.

Nas ilhas oceânicas de Fernando de Noronha, ao largo da costa Nordeste do Brasil, registramos tartarugas-de-pente (Eretmochelys imbricata) visitando estações de limpeza mantidas pelo camarão-palhaço (Stenopus hispidus). Este parece ser o primeiro registro de simbiose de limpeza entre tartarugas marinhas e camarões. Durante o seu forrageamento na planície recifal, as tartarugas visitavam e posavam nas estações regularmente. As mesmas estações eram visitadas por algumas espécies de peixes recifais, que aí posavam e eram limpas pelos camarões. Sugerimos aqui que a simbiose de limpeza entre tartarugas marinhas e camarões seja comum e difundida, porém passa despercebida devido à semelhança superficial entre uma tartaruga que esteja descansando e aquela posando e sendo limpa. Além disso, apresentamos uma origem putativa para a simbiose de limpeza entre tartarugas marinhas e camarões-limpadores, que segue etapas comportamentais relativamente simples.
Keywords: Marine turtle-cleaner shrimp association; cleaning symbiosis; origin of turtle-shrimp association; reef environment; Equatorial West Atlantic; Associação entre tartarugas marinhas e camarões-limpadores; Simbiose de limpeza; origem da associação tartaruga-camarão; ambiente recifal; Atlântico Equatorial Ocidental